Numerical simulation of the debonding process in pull-out tests of near-surface mounted FRP rod in concrete. Issue 3 (21st November 2019) - Chen, Tie-Lin; Tao, Wenbin; Zhu, Wenjun; Zhou, Mozhen
Abstract : Purpose: Near-surface mounted (NSM) fiber-reinforced polymer (FRP) rod is extensively applied in reinforced concrete (RC) structures. The mechanical performances of NSM FRP-strengthened RC structures depend on the bond behavior between NSM reinforcement and concrete. This behavior is typically studied by performing pull-out tests; however, the failure behavior, which is crucial to the local debonding process, is not yet sufficiently understood. Design/methodology/approach: In this study, a three-dimensional meso-scale finite element method considering the cohesion and adhesion failures is presented to model the debonding failure process in pull-out tests of NSM FRP rod in concrete. The smeared crack model is used to capture the cohesion failures in the adhesive or concrete. The interfacial constitutive model is applied to simulate the adhesion failures on the FRP-adhesive and concrete-adhesive contact interfaces. Findings: The present method is first validated by two simple examples and then applied to a practical NSM FRP system. This work studied in detail the debonding process, the bond failure types, the location of peak bond stress, the transmitting deformation in adhesive and the morphology of contact zone. The developed method provides a practical and convenient tool applicable for further investigations on the debonding mechanism for the NSM FRP rod in concrete. Originality/value: A three-dimensional meso-scale finite element method considering the cohesion and adhesion failures is presented to model the debonding failure in NSM FRP-strengthened RC structures. The smeared crack model and the interfacial constitutive model are introduced to develop a convenient approach to analyze the failures in adhesive, concrete and related interfaces. The developed numerical method is applicable for studying the debonding process, the bond failure types, the location of peak bond stress, the transmitting deformation in adhesive and the morphology of contact zone in detail.